The Goldfinch - Tartt, Donna; Pittu, David; Smith, Cheryl; O'Connell, Jared; Hachette Audio (Firm) (New York : Hachette Audio, 2013)
A young boy in New York City, Theo Decker, miraculously survives an accident that takes the life of his mother. Alone and abandoned by his father, Theo is taken in by a friend's family and struggles to make sense of his new life. In the years that follow, he becomes entranced by one of the few things that reminds him of his mother; a small, mysteriously captivating painting that ultimately draws Theo into the art underworld.
Keywords: Young men -- Fiction; Loss (Psychology) -- Fiction; Artists -- Fiction; Self-realization -- Fiction; Audiobooks; New York (N.Y.) -- Fiction; Bildungstromans; Suspense fiction; Audiobooks